Digital Transformation in Hospital Administration: A Bliblimetric Mapping Study - Dwi Pangarsa Wisnumurti; Elsye Maria Rosa (Lembaga Bale Literasi, 2026)
Digital transformation has become a strategic imperative for hospitals, extending beyond isolated technological adoption toward organization-wide changes in governance, workflows, and information systems. However, the research landscape remains multidisciplinary and conceptually diffuse, making it challenging to identify dominant themes and emerging trends.To map the intellectual structure, thematic clusters, and temporal evolution of Scopus-indexed research on digital transformation in hospital administration.A bibliometric mapping study was conducted using Scopus as the sole database. The following query was applied: TITLE-ABS-KEY (“digital transformation”) AND TITLE-ABS-KEY (hospital OR “hospital administration” OR “healthcare administration”), restricted to journal articles, in English published between 2005 and 2025, yielding a final dataset of 345 articles. The final dataset comprised 345 articles. Descriptive bibliometrics were obtained using Scopus Analyzer. The search was conducted on May 2, 2026. Science mapping based on author keyword co-occurrence was conducted using VOSviewer, with a minimum occurrence threshold of five. Publications increased substantially after 2020, with contributions dominated by medicine, computer science, and management. The United Kingdom and the United States were leading contributors. Digital transformation emerged as a central node linked to hospitals, digital health, and health information systems. Four clusters were identified: system-level transformation, digital health innovation, advanced technologies, and implementation-related aspects including readiness and patient safety.Hospital digital transformation research has shifted toward integrated organizational change, emphasizing readiness, maturity, analytics, and safety, but gaps remain in implementation and outcome evaluation